2015
DOI: 10.1007/s10853-015-9200-0
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modeling for predicting peak stress characteristics during hot deformation of hot isostatically processed nickel-base superalloy

Abstract: Hot flow behavior of hot isostatically processed experimental nickel-based superalloy is investigated over temperature and strain rate ranging from 1000-1200°C and 0.001-1 s -1 , respectively by carrying out constant true strain rate isothermal compression tests up to true strain of 0.69. True stress-true strain curves corrected for adiabatic temperature rise exhibited rapid strain hardening followed by flow softening behavior irrespective of temperature and strain rate regimes investigated, although anomalous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The surface temperature increased with increasing strain rate ( Figure 3c), and for 5 s −1 at 1080 • C it even exceeded the carbide solvus (1100 • C), but the test times were too short to allow for any significant carbide dissolution. The increase in temperature due to adiabatic heating agrees with similar studies [26,36].…”
Section: Methodssupporting
confidence: 90%
“…The surface temperature increased with increasing strain rate ( Figure 3c), and for 5 s −1 at 1080 • C it even exceeded the carbide solvus (1100 • C), but the test times were too short to allow for any significant carbide dissolution. The increase in temperature due to adiabatic heating agrees with similar studies [26,36].…”
Section: Methodssupporting
confidence: 90%
“…The observed behavior is typical in alloys showing the occurrence of DRX during hot deformation [38,[44][45][46]. Moreover, it is observed that the peak stress decreases as the temperature increases, which is a conventional behavior and consistent with other reports for nickel-based superalloys [47][48][49][50]. Flow curves of IN718 alloy obtained at the temperature of 1100 °C and at various strain rates from 0.001 to 1 s −1 are also displayed in Fig.…”
Section: Stress-strain Curvessupporting
confidence: 88%
“…10 that the peak stress and the steady-state stress have linear relationship especially for samples compressed at low strain rates. Although in the in literature, there are reports of using both the peak stress [54] and the steady-state stress [16] for formulating the constitutive equations, one should notice that it is not often possible to determine the steady state stress accurately and the adiabatic heating can drop the flow stress at high strain rates. Therefore, it seems that it is better to use the peak stress in constitutive equations rather than steady state stresses.…”
Section: Constitutive Equations Based On Sellars Modelsmentioning
confidence: 99%